PELAKSANAAN PROGRAM TANAMAN PADI OLEH KELOMPOK TANI BULU CEMPA DI DESA NUSA KECAMATAN KAHU KABUPATEN BONE - hasriani hasri; Latang Latang; muhaemin muhaemin (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2022)
This study aims to determine the process of implementing the rice plant program in the Bulu Cempa farmer group in Nusa Village, Kahu District, Bone Regency. This research uses a qualitatif approach with the type of research used is a case study. The subjects of this study were the head of the Bulu Cempa farmer group 1, the treasurer of the Bulu Cempa farmer group and 3 members of the Bulu Cempa farmer group. The data collection process is carried out by 3 methods, namely interview, observation and documentation. The technigues used in data analysis are data reduction, data presentasion, and conclusion drawing. Triangulation is used to explain the validity of the data by using various sources and methods. As for the results of the implementation of the rice plant program in the Bulu Cempa farmer group in the Village of Nusa, Kahu District, Bone Regency, which has increased compared to the previous year, the increase is around 85% of farmer members are more productive and all farmer members already have modern tools in the form of tractors as a tool for their planting process.